2023
DOI: 10.1039/d3cy00319a
|View full text |Cite
|
Sign up to set email alerts
|

Rational design of hydroxyapatite/graphite-supported bimetallic Cu–M (M = Cu, Fe, Co, Ni) catalysts for enhancing the partial hydrogenation of dimethyl oxalate to methyl glycolate

Abstract: Noble metal-free hydroxyapatite (Ca10(PO4)6(OH)2)/graphite composite supported CuCo catalysts are developed and exhibited outstanding stability and catalytic performance in dimethyl oxalate hydrogenation reaction to methyl glycolate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 46 publications
(70 reference statements)
0
6
0
Order By: Relevance
“…34 It has been shown that the ratio between Cu 0 and Cu + has a great influence on the reaction of Cu-based catalysts in DMO gas-phase hydrogenation. Cheng 35 et al , Wang 36 et al , and Abbas 37,38 et al all concluded that the presence of Cu + is beneficial to improve the stability of the catalyst against MG. In this paper, when the Ca loading is 0.1 wt% and the ratio of Cu + is 0.65 is optimal for the MG selectivity.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…34 It has been shown that the ratio between Cu 0 and Cu + has a great influence on the reaction of Cu-based catalysts in DMO gas-phase hydrogenation. Cheng 35 et al , Wang 36 et al , and Abbas 37,38 et al all concluded that the presence of Cu + is beneficial to improve the stability of the catalyst against MG. In this paper, when the Ca loading is 0.1 wt% and the ratio of Cu + is 0.65 is optimal for the MG selectivity.…”
Section: Resultsmentioning
confidence: 99%
“…And the reaction pressure is greatly reduced, basically around 2.5–3 MPa. 9–14 Fig. 1 shows the reaction pathway of MG by gas-phase hydrogenation of DMO.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations